New aspects of altitude adaptation in Tibetans: a proteomic approach. - Gelfi, C; De Palma, S; Ripamonti, M; Eberini, I; Wait, R; Bajracharya, A; Marconi, C; Schneider, A; Hoppeler, H; Cerretelli, P (2004)
A prolonged sojourn above 5500 m induces muscle deterioration and accumulation of lipofuscin in Caucasians, probably because of overproduction of reactive oxygen species (ROS). Because Sherpas, who live at high altitude, have very limited muscle damage, it was hypothesized that Himalayan natives possess intrinsic mechanisms protecting them from oxidative damage. This possibility was investigated by comparing the muscle proteomes of native Tibetans permanently residing at high altitude, second-generation Tibetans born and living at low altitude, and Nepali control subjects permanently residing at low altitude, using 2D gel electrophoresis and mass spectrometry. Seven differentially regulated proteins were identified: glutathione-S-transferase P1-1, which was 380% and 50% overexpressed in Tibetans born and living at high and low altitude, respectively; Delta2-enoyl-CoA-hydratase, which was up-regulated in both Tibetan groups; glyceraldehyde-3-phosphate dehydrogenase and lactate dehydrogenase, which were both slightly down-regulated in Tibetans born and living at high altitude; phosphoglycerate mutase, which was 50% up-regulated in the native Tibetans; NADH-ubiquinone oxidoreductase, slightly overexpressed in Tibetans born and living at high altitude; and myoglobin, which was overexpressed in both Tibetan groups. We concluded that Tibetans at high altitude, and to some extent, those born and living at low altitude, are protected from ROS-induced tissue damage and possess specific metabolic adaptations.